SickKids handbook of pediatric thrombosis and hemostasis - Albisetti Pedroni, Manuela (Karger, 2017)
This updated and extended edition of the SickKids Handbook takes the reader through the entire field of pediatric thrombosis and hemostasis. An introductory section concisely explains the complex pathophysiology of thrombosis and hemostasis. The chapters that follow include practical, evidence-based information on the diagnosis and management of inherited and acquired bleeding disorders and thrombotic events of the venous, arterial, cardiac and central nervous systems that affect children. Special features include practical clinical algorithms and appendices that cite normal laboratory reference ranges, as well as recommended dosages of blood products and major hemostatic agents. A stand-alone chapter is dedicated to developmental hemostasis and bleeding in the neonate. A chapter on antithrombotic therapy in children gives succinct information on the old and new anticoagulants, antiplatelet drugs and thrombolytic agents. Written and reviewed by international experts in the field, this handbook is intended for health care professionals involved in the assessment and care of children with inherited and acquired bleeding and clotting disorders, including general and specialist pediatricians (in particular intensivists, neonatologists, cardiologists/cardiac surgeons, rheumatologists and nephrologists), hematologists/oncologists (pediatric and adult), as well as medical trainees, nurses, nurse practitioners and pharmacists.